Towards Inclusive and Sustainable Development in the Democratic Republic of the Congo - Kostner, Markus (World Bank, Washington, DC, 2012)
In early 1998, the World Bank prepared a paper on the decentralization and participation policies outlined but not fully implemented by the Congolese government in the early days of the third republic. If the country has since receded into war, it is perhaps in part because these ideas were never properly put into practice. Rather than de-legitimizing them, the renewed war makes it even more important that these ideas be heard. Centralization has a long history in the Congo. Though with different justifications and characteristics, central government dominated decision-making and execution during both the colonial period and the second republic. Regarding decision-making, "everything came from above without any explanations". Though local authorities had certain powers, these were more often than not abused rather than used in the interest of the population. Infrequent contact between central authorities and the population resulted in many provinces and territories being, and remaining, enclaved without access to neighboring regions, much less to the outside world.